Productivity gains from exporting: Do Export destinations matter? - Pavel Vacek (Charles University in Prague, Institute of Economic Studies (IES), 2010)
In this paper, I have examined whether exporters benefit by exporting more, and also whether the productivity benefits from exporting more are heterogeneous across export destinations. I have conducted my own data collection field work and built a unique firm-level panel database of Czech manufacturing firms that includes data on the destinations of exports. I have found that firms do benefit from exporting more. However, my results also show that it is necessary to take into account export markets' heterogeneity. I have found that it is only exporting more to developed countries that brings productivity gains.
Keywords: F14; 330; exporting; productivity; spillovers; Außenhandelssektor; Export; Produktivität; Spillover-Effekt; Tschechische Republik